Granular activated carbon enhances volatile fatty acid production in the anaerobic fermentation of garden wastes - Chen, Wenwen; Zeng, Yiwei; Liu, Huanying; Sun, Dezhi; Liu, Xinying; Xu, Haiyu; Wu, Hongbin; Qiu, Bin; Dang, Yan (Frontiers in Bioengineering and Biotechnology, 2023)
Garden waste, one type of lignocellulosic biomass, holds significant potential for the production of volatile fatty acids (VFAs) through anaerobic fermentation. However, the hydrolysis efficiency of garden waste is limited by the inherent recalcitrance, which further influences VFA production. Granular activated carbon (GAC) could promote hydrolysis and acidogenesis efficiency during anaerobic fermentation. This study developed a strategy to use GAC to enhance the anaerobic fermentation of garden waste without any complex pretreatments and extra enzymes. The results showed that GAC addition could improve VFA production, especially acetate, and reach the maximum total VFA yield of 191.55 mg/g VSadded, which increased by 27.35% compared to the control group. The highest VFA/sCOD value of 70.01% was attained in the GAC-amended group, whereas the control group only reached 49.35%, indicating a better hydrolysis and acidogenesis capacity attributed to the addition of GAC. Microbial community results revealed that GAC addition promoted the enrichment of Caproiciproducens and Clostridium, which are crucial for anaerobic VFA production. In addition, only the GAC-amended group showed the presence of Sphaerochaeta and Oscillibacter genera, which are associated with electron transfer processes. Metagenomics analysis indicated that GAC addition improved the abundance of glycoside hydrolases (GHs) and key functional enzymes related to hydrolysis and acidogenesis. Furthermore, the assessment of major genera influencing functional genes in both groups indicated that Sphaerochaeta, Clostridium, and Caproicibacter were the primary contributors to upregulated genes. These findings underscored the significance of employing GAC to enhance the anaerobic fermentation of garden waste, offering a promising approach for sustainable biomass conversion and VFA production.